Expanding the Boundaries of Informal Education Programs: An Investigation of the Role of Pre and Post-education Program Experiences and Dispositions on Youth STEM Learning - Falk, John H.; Meier, David D. (Frontiers in Education, 2021)
For generations educators have been supporting children and youth’s science, technology, engineering, and mathematics (STEM) learning through informal education programming. Such programming includes a wide variety of outdoor education programs, camp programs, and increasingly targeted STEM programs run afterschool, on weekends, and over the summer months. However, despite the positive impacts these programs have, few would argue that these programs could not be improved or be designed to better meet the needs of a broader and more diverse population of learners. Arguably, one major flaw in how most educators have approached the design and improvement of these programs—a flaw that permeates almost all informal STEM education efforts–is that either explicitly or implicitly, the focus of educators has been exclusively on what happens during the program itself. Superficially this seems reasonable. After all, the time children/youth are within the temporal and physical boundaries of the program, class, or museum is the time when educators have maximal control over events. However, given what is known about how people learn (National Academies of Sciences, 2018), we argue that this long-standing approach needs to be reconsidered.